The importance of agriculture in the development of Romanian economy - Raicov Miroslav; Goşa Vasile; Fuchs Adina (University of Szeged Faculty of Agriculture Hódmezővásárhely, 2016)
Agriculture represent one of the most important branches of the Romanian economy. Within performing the suggested analysis we started from the premise that the economy of each country, regardless of developing degree, agriculture, by natural and human resources available, by contributing to the creation of gross domestic product, of gross value added, but also by participating at internal and external trade, obviously holds an important position. Romanian rural economy is currently dominated in a large part by agriculture. Favorable geographical conditions, topography, climate, fertile soils, in addition with workforce, a suitable administrative system, but the connection of rural population to land and animals can make the Romanian agriculture as production branch attractive and profitable to determine economic growth at national level. Thus, we considered necessary to perform an analysis concerning the importance of Romanian agriculture, analysis that represents the basis for finding the most viable solutions to determine this particularly important branch - to relaunch in the development of Romanian rural economy.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz